KONSTRUKSI KAUSATIF ANALITIK DALAM BAHASA INGGRIS DAN BAHASA INDONESIA - Sutar Oktaviana Tampubolon; Mulyadi Mulyadi (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This study discusses the causative constructions of analytics in English and Indonesian. The purpose of this study describes the forms, similarities and differences in Indonesian and English. This research method using descriptive qualitative, with technique refer and note. The results of this study explain the form of the word verb causes (causes) in English in Indonesian verb form word.Keywords: Causative Analytic, English and Indonesian  language.